Enhancing critical thinking development through collaborative authentic assessment: Analyzing persuasive sentence structures in Indonesian language learning - Harsono, Harsono; Amalia, Laili (Institute of Computer Science (IOCS), 2025)
This study explores the effectiveness of collaborative authentic assessment in enhancing students' critical thinking skills in analyzing persuasive sentence structures in the Syntax course. Using a qualitative design with a descriptive-analytical approach, the study involved 20 third-semester students from the Indonesian Language Study Program at Madura University. Data were collected through classroom observations, interviews with students and lecturers, and analysis of advertisement text documents. Thematic analysis was applied to the observation and interview data, and content analysis was used for document analysis. The findings show that the implementation of collaborative authentic assessment significantly improves students' critical thinking skills. Students were able to identify and understand syntactic elements, evaluate their influence on readers, and construct logical arguments. This research contributes theoretically by advancing collaborative-based learning models for the 21st century and provides practical insights for lecturers to design more contextual and interactive teaching approaches.